2013
DOI: 10.1074/jbc.m112.443580
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylation of Serine 399 in LKB1 Protein Short Form by Protein Kinase Cζ Is Required for Its Nucleocytoplasmic Transport and Consequent AMP-activated Protein Kinase (AMPK) Activation

Abstract: Background: LKB1 S activates AMPK despite its lack of Ser-428/431, previously reported as essential for LKB1-mediated activation of AMPK. Results: Ser-399, a novel phosphorylation site in LKB1 S , is essential for AMPK activation. Conclusion: Ser-399 is a PKC -dependent phosphorylation site similar to Ser-428/431 and likely plays a compensatory role. Significance: This study clarifies paradoxical findings regarding the role of the C terminus in LKB1 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
(85 reference statements)
2
13
0
Order By: Relevance
“…Previously, we demonstrated that zinc-induced neuronal death shows apoptotic and necrotic aspects in cortical cultures [ 18 ], and many compounds are involved in zinc toxicity, including PKC, NADPH oxidase, nNOS, PARP-1, ERK, and Egr-1 [ 13 , 14 , 16 , 66 ]. Several reports showed that PKCζ may be an upstream kinase for LKB1 phosphorylation [ 51 , 67 ] we also observed that LKB1 phosphorylation by zinc could be mediated by PKC, and showed that LKB1 phosphorylation was almost completely attenuated by GF109203X, the specific chemical inhibitor of PKC, (Fig. 3e ).…”
Section: Discussionsupporting
confidence: 73%
“…Previously, we demonstrated that zinc-induced neuronal death shows apoptotic and necrotic aspects in cortical cultures [ 18 ], and many compounds are involved in zinc toxicity, including PKC, NADPH oxidase, nNOS, PARP-1, ERK, and Egr-1 [ 13 , 14 , 16 , 66 ]. Several reports showed that PKCζ may be an upstream kinase for LKB1 phosphorylation [ 51 , 67 ] we also observed that LKB1 phosphorylation by zinc could be mediated by PKC, and showed that LKB1 phosphorylation was almost completely attenuated by GF109203X, the specific chemical inhibitor of PKC, (Fig. 3e ).…”
Section: Discussionsupporting
confidence: 73%
“…We found that PSI did not influence phosphorylation of the target of AMPK ACC which would indicate that PKCζ acts downstream of AMPK. Phosphorylation of liver kinase B1 by PKCζ was shown to be necessary for metformin activation of AMPK in A549 distal airway cells . However, our data is supported by evidence from heart cells where metformin increased phosphorylation of PKCζ and that PKCζ activity did not influence metformin phosphorylation of AMPK …”
Section: Discussionsupporting
confidence: 72%
“…As a member of the atypical protein kinase C subfamily, PKCζ phosphorylates LKB1 at Ser-428/431 and mediates activation of AMPK in endothelial cells6061. We measured p-PKCζ levels (Thr410/403) and detected its elevation in LAR- but not PTPσ-overexpressing cells following CSPG stimulation (Fig.…”
Section: Resultsmentioning
confidence: 99%